The Influence of Soft Skills, Work Commitment, and Work Environment on Teacher Performance at SMP Negeri 2 Pare Kediri - Abdillah, Rayan Sya’irul (Formosa Journal of Science and Technology, 2024)
This research aims to determine the influence of soft skills, work commitment and work environment on teacher performance at SMP Negeri 2 Pare Kediri. The variables used in this research are Soft Skills (X1), Work Commitment (X2), Work Environment (X3), and Performance (Y). The research location is Jalan P.K. Nation No. 2, etc. Puhrejo, Ds. Tulungrejo, District. Pare, Kab. Kediri, East Java 64212. With data collection techniques in the form of interviews, questionnaires and observations. Meanwhile, the analysis used uses quantitative methods with multiple linear regression tools using the SPSS version 25.0 software program. Based on tests carried out with partial multiple linear regression analysis, it shows that Soft Skill (X1) has a positive and significant effect on Performance (Y) and Work Commitment (X2) has an insignificant effect on Performance (Y), while the Work Environment variable (X3) has an insignificant effect on Performance (Y). partial has no significant effect on Performance (Y). This is aimed at the significant value for variable X1 5.562>2.012, variable X2 0.460<2.012, and variable Partially, Soft Skills (X1), Work Commitment (X2), and Work Environment (X3) have a positive and significant effect on the performance (Y) of teachers at SMP Negeri 2 Pare Kediri.